Confirmation of Bacterial Leaf Streak Caused by Xanthomonas oryzae pv. oryzicola on Rice in Madagascar - Poulin, L.; Raveloson, H.; Sester, M.; Raboin, L.M.; Silué, D.; Koebnik, R.; Szurek, B. (Scientific Societies, 2014)
Bacterial leaf streak (BLS) caused by Xanthomonas oryzae pv. oryzicola is an important disease of rice. BLS is prevalent in Asia and West Africa, where it was first reported in Nigeria and Senegal in the early 1980s (4). Recently, molecular analysis of strains from Mali (2) and Burkina Faso (5) further confirmed the presence of BLS in West Africa. In Madagascar, BLS symptoms were first reported in the 1980s by Buddenhagen but the causal agent was not unequivocally determined (1). To confirm Buddenhagen's observations using modern molecular typing tools, we surveyed several rice fields in the Antananarivo and Antsirabe districts in March 2013. BLS symptoms were observed on cultivated Oryza sativa grown under both upland and lowland conditions, with a proportion of diseased individuals varying from 30% up to 80%. Symptomatic leaves presenting water-soaked lesions that developed into translucent, yellow streaks with visible exudates at the surface were sampled. One to four centimeter long pieces of diseased leaves were ground using the Qiagen TissueLyser system at 30 rps for 30 s (Qiagen, Courtaboeuf, France). The ground tissue was then macerated in 1 ml of sterile water for 1 h at 4°C. Non-diluted and 10-fold diluted tissue macerates were plated on semi-selective PSA medium (peptone 10 g/liter, sucrose 10 g/liter, glutamic acid 1 g/liter, bacto agar 16 g/liter, actidione 50 mg/liter, cephalexin 40 mg/liter, and kasugamycin 20 mg/liter) and incubated for 3 to 7 days at 28°C. Single, yellow, Xanthomonas-like colonies were isolated on non-selective PSA medium. Diagnostic multiplex PCR was performed on single colonies for pathovar identification (3). Five strains that produced three diagnostic bands corresponding to the X. oryzae pv. oryzicola pattern were further analyzed for pathogenicity on 3-week-old O. sativa cv. Nipponbare plants. Bacteria grown on PSA plates and adjusted to 1 × 108 CFU/ml were infiltrated into rice leaves with a needleless 1-ml syringe (2 × 3 infiltrations per plant and strain). Seven days after incubation in the greenhouse (27 ± 1°C with a 12-h photoperiod), inoculated leaves showed water-soaked lesions that produced yellow exudates corresponding to those initially observed in rice fields and observed for leaves challenged with the X. oryzae pv. oryzicola reference strain BLS256. Symptomatic leaf tissues were ground and plated on non-selective PSA medium, resulting in colonies with typical Xanthomonas morphology that were confirmed as X. oryzae pv. oryzicola by multiplex PCR typing (3), thus fulfilling Koch's postulates. Finally, the five strains were subjected to gyrB sequencing upon PCR amplification using the universal primers XgyrB1F (5′-ACGAGTACAACCCGGACAA-3′) and XgyrB1R (5′-CCCATCARGGTGCTGAAGAT-3′). The 743-bp partial gyrB sequences were 100% identical to the gyrB sequence of strain BLS256. As expected, the gyrB sequence of strains KACC10331, MAFF311018, and PXO99A of the X. oryzae pv. oryzae pathovar respectively showed nine, 16, and 10 mismatches in comparison to the Malagasy strains, thus further supporting that they belong to the pathovar oryzicola.